Editorial: The contradictions of green extractivism - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
Uneasy contradictions in development policy in Africa were laid bare in February 2025 by a disastrous accident at a copper mine in Zambia. An unmonitored and badly constructed tailings dam failed, releasing some 50 million litres of toxic mine sludge to pollute the Kafue River. Fish died, livestock were poisoned, farmers’ crops were destroyed and people along the river, the longest in Zambia, lost their water supply. As the poisoned water flowed downstream, engineers had to cut off water to Zambia’s second biggest city Kitwe, 30km from the mine with a population of over 600,000. By the date of publication, the scale of the catastrophe was still to be measured.